Capital Efficiency and Liquidity on the Profitability of Companies Registered in the BEI Cosmetics and Household Supplies Sub Sector - Anizar, Sriyunia; Suzana, Suzi; Jakiroh, Jakiroh; Aida, Aida (Journal of Social Science, 2024)
The aim of this research is to determine the effect of working capital and liquidity on the company's profitability. The method used is causal quantitative, which looks at cause and effect relationships or relationships that are influenced and influenced. Data obtained from the Indonesian Stock Exchange with 10 populations. Sample selection used purposive sampling with a total of 30 data analyzed using multiple linear regression analysis techniques. The t hypothesis test explains that working capital efficiency has an influence on profitability while liquidity has no influence on profitability. The results of the hypothesis f test explain that working capital and liquidity have a simultaneous influence on profitability if tested simultaneously. Another result is 66.7% profitability influenced by working capital and liquidity variables.